Consumer behaviour towards online shopping - Gowripeddi Hari Kumar; P, Dadapeer (Journal of Management and Science, 2022)
Everything in the world is shifting towards digital which is no exception and ultimately the market as well. The place where buyers and sellers meet together in virtual form and exchange goods and services in online is called E – Commerce. It is also known as I – Commence. The fastest growing media in recent times is the Internet. It is the foundation of a new era. Online shopping is one of the very fast rising e-commerce platform.Online stores are always available to the customer 24 hours a day (24 x 7) and the customer can use the service from his office or from home or anywhere. A successful web store is not only about making the website looking beautiful with the active technical features listed in many search engines but also about the convenience and satisfaction of the users. The main goal of this research is to assess and understand the basic features of online shopping. It is an attempt to provide online marketers with a structured framework for adjusting their online business plans and to examine the behavior of online consumers.